Spontaneous Growth of 3D Framework Carbon from Sodium Citrate for High Energy‐ and Power‐Density and Long‐Life Sodium‐Ion Hybrid Capacitors. Issue 10 (18th December 2017) - Yang, Bingjun; Chen, Jiangtao; Lei, Shulai; Guo, Ruisheng; Li, Hongxia; Shi, Siqi; Yan, Xingbin
Abstract: Carbon sheets with 3D architectures, large graphitic interlayer spacing, and high electrical conductivity are highly expected to be an ideal anode material for sodium‐ion hybrid capacitors (SIHCs). Pursuing a simple synthesis methodology and advancing it from the laboratory to industry is of great importance. In this study, a new approach is presented to prepare 3D framework carbon (3DFC) with the above integrated advantages by a direct calcination of sodium citrate without aid of any additional carbon source, template, or catalyst. The first‐principle calculations verify that the large interlayer spacing and the curvature structure of 3DFC facilitate the sodium ion insertion/extraction. As a consequence, the optimal 3DFC sample exhibits high reversible capacity as well as excellent rate and cycling performance. On this basis, a dual‐carbon SIHC is fabricated by employing 3DFC as battery‐type anode and 3DFC‐derived nanoporous carbon as capacitor‐type cathode. It is able to deliver high energy‐ and power‐density feature as well as outstanding long‐term cycling stability in the potential range of 0–4.0 V. This study may open an avenue for developing high‐performance carbon electrode materials and pushes the practical applications of SIHCs a decisive step forward. Abstract : A simple, low‐cost, and large‐scale preparation of 3D framework carbon (3DFC) with large interlayer spacing, curved interface, and high conductivity is proposed. The as‐prepared 3DFC anode exhibits excellent sodium storage performance. On this basis, an advanced dual‐carbon sodium‐ion hybrid capacitor is fabricated by employing such 3DFC as battery‐type anode and 3DFC‐derived nanoporous carbon as capacitor‐type cathode.